(untitled) (Physical Education, Health and Social Sciences, 2026)
All economic sectors worldwide are facing significant threats due to climate change, but the agricultural sector is more vulnerable due to its high level of dependency of livelihood in the community. The study was designed with the objectives to analyze the factors that affect tomato productivity due to climate change and role of extension field in tackling these challenges. The sample of 135 respondents was selected from total of 450 farmers in the study area for conducting and executing this study. It was found that 46.0% of the respondents laid the in the age group of 18-35 years old, while 20.7% respondents had age of above 50 years, 30.4% of the respondents claimed drought condition affect their productivity of tomato crop, while 16.3% of the respondents claimed floods in the area hardly affect their tomato crop. Majority (77.0 %) of the respondents were agreed that there was an increase in temperature and number of sunny days, while 6.7% of the respondents was disagreeing with this. Majority (61.5%) of the respondents were agreed with frequency of heavy rains increased due to climate change, while 13.3% of the respondents disagreed with this. Study found that 68.9% of the respondents were agreed with fluctuation in rain patterns while 10.4% of the respondents were disagreed with this. most (55.6%) of the respondents cultivated tomato on up to 2 acres of land, while 6.7% of the respondents cultivated on more than 4 acres in 2024. most (57.0%) of the respondents cultivate tomato on up to 2 acres of land while 6.7% cultivate tomato crop on above 4 acres of land in 2025. Based on the conclusion it is recommended that Agricultural extension services should be strengthened to provide farmers with regular, practical training on tomato production and climate adaptation. Further recommended that Access to timely and accurate weather information should be improved through mobile alerts, radio, and local advisory services, enabling farmers to make informed decisions about irrigation, sowing, and pest control.